Penerapan Metode Kaisa dalam Memahami Al-Qur’an pada Anak Usia Dini di RA Anak Shaleh Suwayuwo - Fikriyah, Adela Tsamrotul (Lembaga Yasin AlSys, 2024)
God has given the Qur'an as a guide and instruction for humanity, so that they can understand His will and pleasure. Introduction to and understanding of the Qur'an are essential aspects of religious education from an early age, especially in Early Childhood. The Kaisa method is one of the engaging ways to understand the Qur'an. This research aims to examine the application of the Kaisa method in understanding the Qur'an in early childhood. The author will identify the steps and challenges that arise in the implementation of this method and how it can contribute to the understanding of the Qur'an and the moral and religious development of early childhood. The research method applied is qualitative research in the form of descriptive research, with data collection and gathering techniques using observation, interviews, and documentation. The results of this study state that the application of the Kaisa method at the RA Anak Shaleh Suwayuwo involves three main steps, including the planning, implementation, and evaluation stages. In the application of the Kaisa method, supportive factors include high student motivation and a conducive learning environment.